Prussian blue nanotechnology in the treatment of spinal cord injury: application and challenges - Gu, XiaoPeng; Zhang, SongOu; Ma, WeiHu (Frontiers in Bioengineering and Biotechnology, 2024)
Spinal cord injury (SCI) is a serious neurological condition that currently lacks effective treatments, placing a heavy burden on both patients and society. Prussian blue nanoparticles exhibit great potential for treating spinal cord injuries due to their excellent physicochemical properties and biocompatibility. These nanoparticles have strong anti-inflammatory and antioxidant capabilities, effectively scavenge free radicals, and reduce oxidative stress damage to cells. Prussian blue nanotechnology shows broad application potential in drug delivery, bioimaging, cancer therapy, anti-inflammatory and oxidative stress treatment, and biosensors. This article reviewed the potential applications of Prussian blue nanotechnology in treating spinal cord injuries, explored the challenges and solutions associated with its application, and discussed the future prospects of this technology in SCI treatment.